The Synergy of Academics and Industry Practitioners in Improving Tourism Services at Kamuella Resort - Lubis, Arina Luthfini; Wibowo, Andri; Wardani, Yudha; Pratama, Oktora Aji (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
This community service program focuses on improving tourism services at Kamuella Resort through a synergy between academics and industry practitioners, aiming to respond to the need for high-quality services amidst rising tourist expectations, especially after the pandemic. This collaboration blends academic insights on traveler trends and preferences with practical expertise in the daily operations of the industry, resulting in a comprehensive and sustainable service improvement strategy. Implementation methods included intensive training of employees in customer service skills, improvement of standard operating procedures (SOPs) to align with the latest quality standards, and strengthening cross-departmental coordination to ensure service consistency in all aspects of resort operations. In addition, regular evaluations are conducted to monitor the implementation of SOPs and identify opportunities for improvement, so that employees' capabilities continue to improve and are able to meet guest expectations more effectively. The results of this program can be seen in improved employee skills, operational efficiency, and guest satisfaction as reflected in positive reviews and increased customer loyalty. In addition to the benefits to the resort, the program also created a model of collaboration that can be replicated in other tourist destinations, ultimately contributing to improved service standards in the local tourism sector. The overall program demonstrates the importance of partnerships between academia and industry to create responsive, high-quality services and build a reputation that supports the competitiveness and sustainability of the tourism sector.